Research on the Application of Nano-Additives in Gel-like Lubricants - Han Peng; Zihao Meng; Linjian Shangguan; Lei Liu; Can Yang; Lingxi Guo (Gels, 2025)
In the field of mechanical motion, friction loss and material wear are common problems. As one of the essential components for enhancing the lubricating performance of gel-like lubricants, nano-additives leverage their unique physical and chemical properties to form an efficient protective film on friction surfaces. This effectively reduces friction resistance and inhibits wear progression, thereby playing a significant role in promoting energy conservation, emissions reduction, and the implementation of green development principles. This study first introduces the physical and chemical preparation processes of gel-like lubricant nanoadditives. It then classifies them (mainly based on metal bases, metal oxides, nanocarbon materials, and other nanoadditives). Then, the performance of gel-like lubricant nano-additives is evaluated (mainly in terms of anti-wear, friction reduction, oxidation resistance, and load carrying capacity), and the surface analysis technology used is described. Finally, we summarize the application scenarios of gel-like lubricant nano-additives, identify the challenges faced, and discuss future prospects. This study provides new insights and directions for the design and synthesis of novel gel-like lubricants with significant lubricating and anti-wear properties in the future.